Do gun buybacks save lives? Evidence from panel data - Andrew Leigh; Christine Neill (Institute for the Study of Labor (IZA), 2010)
In 1997, Australia implemented a gun buyback program that reduced the stock of firearms by around one-fifth. Using differences across states in the number of firearms withdrawn, we test whether the reduction in firearms availability affected firearm homicide and suicide rates. We find that the buyback led to a drop in the firearm suicide rates of almost 80 per cent, with no statistically significant effect on non-firearm death rates. The estimated effect on firearm homicides is of similar magnitude, but is less precise. The results are robust to a variety of specification checks, and to instrumenting the state-level buyback rate.
Keywords: I12; K14; 330; Firearms ownership; homicide; suicide; panel data; Waffe; Öffentliche Beschaffung; Waffenrecht; Wirkungsanalyse; Selbstmord; Kriminalität; Australien